Positive abundance–elevational range size relationship weakened from temperate to subtropical ecosystems. Issue 11 (24th July 2021) - Hu, Yiming; Scheffers, Brett; Pan, Xinyuan; Hu, Huijian; Zhou, Zhixin; Liang, Dan; Wenda, Cheng; Wen, Zhixin; Gibson, Luke
Abstract: Describing the patterns and revealing the underlying mechanisms responsible for variations in community structure remain a central focus in ecology. However, important gaps remain, including our understanding of species abundance. Most studies on abundance‐based relationships are from either temperate ecosystems or tropical ecosystems, and few have explicitly tested abundance‐based relationships across a temperate to tropical ecotone. Here, we use a comprehensive dataset of breeding birds across elevation spanning a temperate to subtropical gradient in the Himalayas–Hengduan Mountains of China to examine the relationship between species abundance and (a) elevational range size, (b) body size, (c) elevational range centre and (d) endemicity. We tested a priori predictions for abundance–elevational range size relationship, abundance–body size relationship and abundance–elevational range centre relationship, and explored how these relationships change along this temperate to subtropical mountain ecosystem. We found that species abundance was significantly positively correlated with elevational range size across the study sites, demonstrating the key importance of elevational range size towards species abundance. Body size and elevational range centre are weakly correlated with abundance. A novel finding of our study is that the abundance–elevational range size relationship gradually weakened from temperate to subtropical ecosystems, adding to a growing body of evidence suggesting that abundance–elevational range size tracks a temperate to tropical ecotone. Our study demonstrates that abundance range–size relationship can transition across ecotones where faunas of different evolutionary origins converge. Furthermore, measuring abundance relationships across different environmental variables at the same spatial scale with comparable biogeography is a key strategy that can reveal the underlying mechanisms behind abundance patterns. Abstract : The positive abundance–elevational range size relationship of birds gradually weakened from temperate to subtropical ecosystems in the Himalayas–Hengduan Mountains of China, adding to a growing body of evidence suggesting that abundance–elevational range size tracks a temperate to (sub)tropical ecotone, and can transition across ecotones where faunas of different evolutionary origins converge. 摘要: 描述群落结构及揭示其建群机制一直是生态学研究的焦点, 但是我们对相关机制的认识依然不足, 如物种多度。物种多度关系的研究 (如多度‐分布范围关系) 大多在单一的生态系统内进行, 很少跨越不同的气候带 (如温带到热带) 检验多度关系的变化规律。 本研究在中国喜马拉雅‐横断山区, 沿温带到亚热带的气候梯度, 在三个垂直生态系统探究繁殖鸟类物种多度与 (1) 海拔分布范围、 (2) 体型、 (3) 海拔范围中心和 (4) 物种特有性之间的关系。 我们检验了多度‐海拔分布范围关系、多度‐体型关系和多度‐海拔范围中心关系在不同气候区 (温带: 中喜马拉雅山;过渡性温带: 东喜马拉雅山;亚热带: 高黎贡山) 的先验预测, 并明确了这些关系在不同气候带的山地生态系统中的变化规律。 我们在三个研究点都发现了显著的正相关多度‐海拔分布范围关系, 这表明海拔分布范围对物种多度具有重要的影响。然而, 体型和海拔范围中心与多度的关系则很弱。重要的是, 我们发现了多度‐海拔分布范围关系 (斜率和拟合度) 从温带到亚热带生态系统逐渐减弱的规律。 多度‐海拔分布范围关系从温带到亚热带逐渐减弱的趋势很好地反映了过去不同地区相关研究的结果, 即多度‐分布范围关系在温带多为正相关, 在热带则趋于表现为负相关或不相关。该趋势也证明了多度‐分布范围关系在不同进化起源的动物群中会有不同的表现。此外, 本研究强调使用空间尺度不匹配的数据拟合多度‐分布范围关系会阻碍对其正确的解读。为了准确地描述物种多度格局并揭示其潜在机制, 我们必须在可比较的空间尺度中对多度及相关变量进行分析。